2018
DOI: 10.1158/0008-5472.can-17-3149
|View full text |Cite
|
Sign up to set email alerts
|

The Endosomal Protein CEMIP Links WNT Signaling to MEK1–ERK1/2 Activation in Selumetinib-Resistant Intestinal Organoids

Abstract: MAPK signaling pathways are constitutively active in colon cancer and also promote acquired resistance to MEK1 inhibition. Here, we demonstrate that -mutated colorectal cancers acquire resistance to MEK1 inhibition by inducing expression of the scaffold protein CEMIP through a β-catenin- and FRA-1-dependent pathway. CEMIP was found in endosomes and bound MEK1 to sustain ERK1/2 activation in MEK1 inhibitor-resistant BRAF-mutated colorectal cancers. The CEMIP-dependent pathway maintained c-Myc protein levels thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…To identify potential therapeutic targets derived from CAFs, we selected genes with frequent decrease (in ≥5 pairs) and also with gene products likely to be localised in plasma membrane or extracellular space. There were 34 such genes, and included a WNT ligand, WNT5A ,16 32 and its regulator, CEMIP ,33 stem cell niche factors, such as NOG ,34 GREM1 35 and EDIL3 ,36 and growth factors, such as IGF2 37 (online supplementary figure S4A). This result supported the promoting effect of CAF-derived CM on cell growth and migration and the idea of isolating targets for cancer-starving therapy based on H3K27me3 changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify potential therapeutic targets derived from CAFs, we selected genes with frequent decrease (in ≥5 pairs) and also with gene products likely to be localised in plasma membrane or extracellular space. There were 34 such genes, and included a WNT ligand, WNT5A ,16 32 and its regulator, CEMIP ,33 stem cell niche factors, such as NOG ,34 GREM1 35 and EDIL3 ,36 and growth factors, such as IGF2 37 (online supplementary figure S4A). This result supported the promoting effect of CAF-derived CM on cell growth and migration and the idea of isolating targets for cancer-starving therapy based on H3K27me3 changes.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies defined essential factors for maintenance of gastric epithelial stem cells, WNT signal activators, EGF, FGF10, BMP inhibitors, and TGF-β inhibitors 39–41. Many of them were among the genes with decreased H3K27me3 in CAFs, such as WNT signal activator ( WNT5A and CEMIP 33), and BMP inhibitors (Noggin, NOG 34 and GREM1 42). Potential therapeutic targets included a well-known growth factor IGF2 ,37 and an angiogenesis mediator, EDIL3 36.…”
Section: Discussionmentioning
confidence: 99%
“…IL27RA might participate in immune regulation in CNS (Iwasaki et al, 2015;Yoshida and Hunter, 2015). CEMIP may be related to brain function and development (Yoshino et al, 2017(Yoshino et al, , 2018, MEK/ERK-induced Schwann-cell dedifferentiation (Boerboom et al, 2017), immune response in glioblastoma (Motaln et al, 2012), and WNT signaling (Li et al, 2017;Duong et al, 2018;Liang et al, 2018). It was frequently reported in colorectal cancers as well (Fink et al, 2015;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that organoid can serve as an excellent model for evaluating specific responses of cancer patients [ 26 , 69 , 81 , 95 , 96 ]. Besides, it also can be an extraordinary alternative to explore the detailed causal epigenetic and genetic alterations underlying drug resistance [ 97 ]. Several organoid biobanks of cancers so far have been established for the purposes of identifying and testing novel drugs [ 37 , 38 , 98 ], and healthy organoids can be utilized to test toxicology.…”
Section: Organoids In Drug Developmentmentioning
confidence: 99%